Beautiful lies - Clark, Clare (Houghton Mifflin Harcourt, 2012)
A tale inspired by a true story follows the experiences of Scottish aristocrat's wife Maribel Campbell, a self-proclaimed Chilean heiress who in late Victorian London finds her husband's career threatened by a notorious journalist's investigation into her true past.